Analisis Pemanfaatan Sewa Barang Milik Daerah (BMD) terhadap Peningkatan Pendapatan Asli Daerah (PAD) Kabupaten Sumbawa Barat Tahun 2017-2019 - Ahdi Topan Sofyan; Ryan Hidayat; Eko Suryaningsih (Syntax Idea, 2021)
The purpose of this study is (1) to know the tourism tourism of Regional Property Tourism (BMD) where the increase in Regional Native Income (PAD) West Sumbawa Regency in 2017-2019; (2) For the level of effectiveness of the business fund of Regional Property Business (BMD) to the revenue of The Original Region (PAD) west Sumbawa Regency year 2017-2019; (3) For the level of efficiency level of regional property owned enterprises (BMD) around the revenue of The Original Region (PAD) Sumbawa Regency year 2017-2019; (4) To know from the regional property business fund (BMD) to the Regional Revenue Revenue (PAD) West Sumbawa Regency year 2017-2019. This type of research uses quantitative research. Data collection techniques which is how to draw and good name. Life and samples in this study are the Original Regional Income Report (PAD) year 2017-2019. Data analysis of techniques in which analysis of comments, analysis of efficiency ratios, analysis of efficiency ratios and analysis of trends by means of energy squares. The results of the research: (1) There is a share of regional property (BMD) to the Regional Original Income (PAD) in 2017 of 0.42%; In 2018 by 1.12%; and 2019 at 0.79%. The central level level of regional property rental (BMD) to Regional Original Income (PAD) is 96.15% in 2017; In 2018 it was 100.51%; and In 2019 60.54% was categorized as less. The market for the use of Regional Property Technology (BMD) to Regional Native Income (PAD) is categorized as believing, in 2017 amounted to 19.32%; In 2018 it was 16.61% and 2019 was 18.00%. (4) 0.59% of 2017 trend results; In 2018 it was 0.78%; In 2019 amounted to 0.96%, and the results of the t-test can be concluded that there is a rental income of Regional Property (BMD) to the Regional Native Income (PAD) in West Sumbawa Regency in 2017-2019. Inventory of this thesis research also immobilizes the Local Government so that the inventory of goods belonging to the region both land, equipment and machinery and machinery and buildings on which the goods card is not used for waste form in order to get revenues native districts in West Sumbawa.